Effects of high-intensity interval training on heart rate variability during exercise - Fronchetti, L.; Nakamura, F. Y.; De-Oliveira, F. R.; Lima-Silva, A. E.; De Lima, J. R. P. (Journal of Exercise Physiology online, 2007)
Heart rate variability (HRV), as indicated by SD1, decreases gradually during progressive incremental exercise, and presents a saturation point at ~3 ms (HRV threshold). The objective of this study was to assess the effects of high-intensity interval training on HRV threshold and HR-work rate curve during progressive incremental exercise. Twenty subjects were randomly assigned to two groups: training (T) and control (C). They underwent a progressive incremental test until exhaustion before and after experimental periods. The T group performed nine sessions of high intensity interval training on a cycle ergometer during 3-weeks (1-min at 130% of maximal aerobic work rate with 1-min rest intervals until volitional exhaustion). HRV was determined using the plot method of Poincaré. High intensity training induced an increase of HRV threshold in the T group (from 95.30 ± 21.9 to 130.0 ± 31.7 W, p = 0.05), but had no effect in the C group. Submaximal HR decreased significantly in T group but did not decrease in the C group. We concluded that 3-weeks of high intensity training induced an increase of HRV threshold and a decrease of submaximal HR. These alterations may be due to the delay of parasympathetic withdrawal during incremental exercise. ABSTRACT FROM AUTHOR